Peningkatan keterampilan pemecahan masalah soal cerita matematika dengan menggunakan model probing-prompting learning (ppl) pada peserta didik sekolah dasar - Kusniyah Ningrum; Riyadi Riyadi; Sukarno Sukarno (Universitas Sebelas Maret, 2020)
The purpose of research is improve problem solving skills in the stories matter by using the Probing – Prompting Learning (PPL) models. This research is Classroom Action Research with two cycles. The subjects of this research were students of IV class at SD Negeri Tegalrejo in the 2019/2020 academic year, totaling 24 students. This research uses data collection techniques in the form of interviews, observations, tests, and documentation with data analysis of source triangulation and technique triangulation. The analysis of the data used is the interactive analysis model of Miles-Huberman. The initial conditions of problem solving skills of IV class students showed 25% classically. The cycle resulting in a percentage of 54,16% in classical, and the study continued with the second cycle with the percentage of 75% in classical terms. Based on the result of the research, it can be conclude that the ability to solve water cycle problems on IV students of SD Negeri Tegalrejo in the 2019/2020 academic year can be improved through the Probing – Prompting Learning models.